Penentuan Calon Suami Dengan Cara Lotre Akibat Kawin Hamil Perspektif Fungsionalisme Struktural - Laila Fitrotul Aziza; Abid Rohmanu; Rohmah Maulidia (Institut Agama Islam Negeri Ponorogo, 2025)
This research is a qualitative study with a descriptive-analytical (field research) approach aimed at examining the practice of selecting a prospective husband through a lottery mechanism to solve cases of out-of-wedlock pregnancy, viewed from the perspective of structural functionalism. The primary focus of this study is the social phenomenon occurring in the community of Purwosari Village, Babadan Sub-district, Ponorogo Regency, where a lottery marriage is conducted to determine which man must marry a pregnant woman when the actual father is unknown. The data were obtained through direct field observations, in-depth interviews with community figures, and documentation studies. The primary data sources include local community members, victims, family members, religious leaders, and village officials. Data collection methods comprised participatory observation, in-depth interviews, and document analysis. The data were analyzed qualitatively using Talcott Parsons’ structural functionalism theory, particularly the four AGIL schemes (adaptation, goal attainment, integration, and latency), along with Peter L. Berger’s theory of social construction through the stages of externalization, objectification, and internalization. The results show two main findings: (1) The lottery marriage practice due to out-of-wedlock pregnancy is perceived by some community members as a pragmatic solution, despite contradicting religious norms and legal standards that only permit marriage with the actual biological father; (2) Although considered a temporary solution, this practice raises negative social implications such as normalizing premarital sexual behavior and creating instability in family structures. In conclusion, lottery marriage is a form of social adaptation to urgent situations, yet it cannot serve as a long-term solution due to its moral and legal contradictions.